A spatial and integrated flood risk diagnosis: Relevance for disaster prevention at Ourika valley (High Atlas-Morocco). Issue 5 (7th October 2019) - Bennani, Oumaima; Druon, Ernest; Leone, Frédéric; Tramblay, Yves; Saidi, Mohamed El Mehdi
Abstract : Purpose: The purpose of this paper is to identify vulnerable areas for flood hazard and to analyze stakes exposed in touristic valley of Morrocan mountains. The three goals are: methodological (low-cost diagnosis without starting data), operational (to show the risk and identify avenues of prevention in Ourika) and incentive (to reproduce this on other sectors in Morocco). Design/methodology/approach: The vulnerability of three areas of the Ourika valley (the most frequented) was assessed by a hydro-geomorphological study, human frequentation surveys and risk indices at the building scale. Findings: Surveys carried out in the field allowed the identification of areas with high risk, the evaluation of the buildings' vulnerability and the frequentation of the valley. Evacuation plans, allowing easy access to potential refuges in case of flood, were finally proposed. Originality/value: The reproducible, inexpensive and relevant nature of the approach (integrated and spatialized) helps in decision making and facilitating dialogue for prevention.